Effectiveness of interventions on conscience: Findings of a systematic review - Lamb, Christina M (Nursing ethics, 2025)
Research indicates that conscience is an asset to healthcare professional’s personal and professional practice. However, little work has been done to support healthcare professionals to use and understand their conscience for moral decision-making. Disparity exists between international and national bodies that value conscience for healthcare professionals and the paucity of practice supports available to formally assist healthcare professionals to openly discuss and then navigate their moral decisions arising from their conscience. Therefore, the purpose of this systematic review was to examine the effectiveness of existing interventions aimed at supporting healthcare professionals to understand and use their conscience for healthcare practice. This review was conducted and reported following the Preferred Reporting Items for Systematic Reviews and Metanalyses. International, interdisciplinary databases including Medline, Embase, PsycINFO, CINAHL, Academic Search Complete, ATLA Religion, Religion and Philosophy Collection, PhilPapers, Scopus and Cochrane Controlled Register of Trials were searched and quantitative as well as qualitative outcomes were reported. We found 11 studies that met the inclusion criteria and underwent data extraction and synthesis. Five interventions were identified that aimed to address aspects of HCP’s conscience. No interventions were identified that aim to support healthcare professionals to understand or use their conscience for moral decision-making in practice. Empirical and humanities research indicates that conscience is essential to healthcare practice, but issues of conscience remain a polarizing experience for many HCPs. Intervention and education-based research are therefore needed to support HCP’s understanding and use of conscience for practice.